2016
DOI: 10.1007/s11356-016-6545-0
|View full text |Cite
|
Sign up to set email alerts
|

New criteria for the characterization of traditional East Asian papers

Abstract: We report a pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) method capable of analyzing traditional East Asian papers. The method proposed is based on rapid and easy single step Py-GC/MS analysis that can be carried out with a minimum amount of matter, in the few microgram range. Three reference papers manufactured from kozo (Broussonetia kazinoki Siebold & Zucc.), mitsumata (Edgeworthia chrysantha Lindl.), and gampi (Wikstroemia sikokiana Franch. & Sav.) with the traditional hand paper making proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
(46 reference statements)
2
20
0
Order By: Relevance
“…Cellulose is a linear homopolysaccharide composed of β-D-glucopyranoside units linked by (1→4) bonds (Keheyan 2008). The thermal decomposition of cellulose is the result of two competing reactions: a dehydration reaction which yields anhydrocellulose and the depolymerisation of cellulose which yields primarily levoglucosan and minor anhydrosugar components (Avataneo and Sablier 2016).…”
Section: Results and Discussion Four Typical Chinese Handmade Papers Analyzed Via Py-gc/msmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose is a linear homopolysaccharide composed of β-D-glucopyranoside units linked by (1→4) bonds (Keheyan 2008). The thermal decomposition of cellulose is the result of two competing reactions: a dehydration reaction which yields anhydrocellulose and the depolymerisation of cellulose which yields primarily levoglucosan and minor anhydrosugar components (Avataneo and Sablier 2016).…”
Section: Results and Discussion Four Typical Chinese Handmade Papers Analyzed Via Py-gc/msmentioning
confidence: 99%
“…Assuming that the paper fibers may still retain the specific biochemical constituents of their raw materials after the papermaking process, this study was conducted. It has been reported that pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) was successfully used for the differentiating East Asian handmade paper (kozo paper, mitsumata paper, and gampi paper) according to the biochemical markers of origin of the plant raw materials, since each paper has characteristic pyrolysis fingerprints (Avataneo and Sablier 2016;Han et al 2016Han et al , 2017. In addition, Py-GC/MS was used to analyze the thermal cracking behaviors of cigarette papers made of wood pulp and hemp pulp (Zhang et al 2017;Sun et al 2008); and to estimate the age of documents through paper analyses (Keheyan 2008;Ortiz-Herrero et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…69 Heullimtteugi Hanji product from cellulose pyrolysis, a characteristic feature of cellulosic material pyrolysis that has been previously elaborated (Fig. 7A) [3,40,48,49].…”
Section: The Chemical Profiles Of Raw Fibersmentioning
confidence: 94%
“…Terpenic compounds with the characteristic ions of m/z at 218, 203, 189 was identified and characterized in the pyrolysis of Hanji that are in accord to papermaking fibers from the Moraceae family [40,41,51,52]. It can be seen from the total ion chromatogram (TIC) that these terpenic compounds elute in the plant marker region (defined as region of interest, ROI) at a comparatively high temperature (Fig.…”
Section: The Chemical Profiles Of Raw Fibersmentioning
confidence: 99%
See 1 more Smart Citation